Synthesis and radical scavenging activity of 6-hydroxyl-4-methylcoumarin and its derivatives - Jumal J.; Ayomide A.F. (American Institute of Physics Inc., 2024)
Four compounds of coumarin derivatives namely 6-hydroxyl-4-methylcoumarin (I), 6-hydroxyl-4-methyl-5-(p-nitrophenyl azocoumarin) (II), 6-hydroxyl-4-methyl-5,7-(bis-p-nitrophenyl azocoumarin) (III) and 6-hydroxyl-4-methyl-5,7-(bis-p-chlorophenyl azocoumarin) (IV) were successfully synthesized. These compounds were prepared by reacting hydroquinone with ethylacetoacetate and selected anilines which are chloro and nitro aniline. All synthesized compounds were characterized by CHN micro-elemental analysis, 1H Nuclear Magnetic Resonance (NMR) and Fourier Transform Infrared (FTIR) spectroscopic methods. The infrared spectra of these compounds exhibited five important stretching vibrations: ?(-OH), ?(C=O), ?(C=C), ?(C-O) and ?(C-N) at 3441-3359 cm-1, 1604-1632 cm-1, 1581-1496 cm-1, 1331-1225 cm-1, 1251-1109 cm-1, respectively. 1H NMR spectra of these compounds show the presence of proton aromatic, proton methyl and proton pyrone ring with the chemical shift at ?H 7.00-8.70 ppm, ?H 2.20-2.50 ppm and ?H 6.10-6.90 ppm, respectively. CHN analysis results of all compounds are in good agreement with the calculated values. All the synthesized compounds were evaluated for their antioxidant activity using DPPH method and ascorbic acid used as the standard. UV-Vis spectroscopic technique was used to investigate the absorbance of these compounds. Compound (II) shows high antioxidant activities compared to compound (I), (III) and (IV) which show moderate to low activities. 2018 Author(s).